Resting state BOLD-perfusion coupling patterns using multiband multi-echo pseudo-continuous arterial spin label imaging - Alexander D. Cohen; Stefano Moia; G. Bruce Pike; César Caballero-Gaudes; Yang Wang (Scientific Reports)
Abstract The alteration of neurovascular coupling (NVC), where acute localized blood flow increases following neural activity, plays a key role in several neurovascular processes including aging and neurodegeneration. While not equivalent to NVC, the coupling between simultaneously measured cerebral blood flow (CBF) with arterial spin labeling (ASL) and blood oxygenation dependent (BOLD) signals, can also be affected. Moreover, the acquisition of BOLD data allows the assessment of resting state (RS) fMRI metrics. In this study a multiband, multi-echo (MBME) pseudo-continuous ASL (pCASL) sequence was used to collect simultaneous BOLD and ASL data in a group of healthy control subjects, and the patterns of BOLD-CBF coupling were evaluated. Coupling was also correlated with the BOLD RS measures. The variability, reproducibility, and reliability of the metrics were also computed in a multi-session subgroup. Areas of higher coupling were observed in the visual, motor, parietal, and frontal cortices and corresponded to major brain networks. Areas of significant correlation between coupling and BOLD RS measures corresponded to areas of heightened coupling. Higher variability and lower reliability were found for coupling metrics compared to BOLD RS metrics. These results indicate BOLD-CBF coupling metrics may be useful for studying neurovascular physiology.